3(x-5)-(2x+4)=-x+7

Simple and best practice solution for 3(x-5)-(2x+4)=-x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)-(2x+4)=-x+7 equation:


Simplifying
3(x + -5) + -1(2x + 4) = -1x + 7

Reorder the terms:
3(-5 + x) + -1(2x + 4) = -1x + 7
(-5 * 3 + x * 3) + -1(2x + 4) = -1x + 7
(-15 + 3x) + -1(2x + 4) = -1x + 7

Reorder the terms:
-15 + 3x + -1(4 + 2x) = -1x + 7
-15 + 3x + (4 * -1 + 2x * -1) = -1x + 7
-15 + 3x + (-4 + -2x) = -1x + 7

Reorder the terms:
-15 + -4 + 3x + -2x = -1x + 7

Combine like terms: -15 + -4 = -19
-19 + 3x + -2x = -1x + 7

Combine like terms: 3x + -2x = 1x
-19 + 1x = -1x + 7

Reorder the terms:
-19 + 1x = 7 + -1x

Solving
-19 + 1x = 7 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-19 + 1x + x = 7 + -1x + x

Combine like terms: 1x + x = 2x
-19 + 2x = 7 + -1x + x

Combine like terms: -1x + x = 0
-19 + 2x = 7 + 0
-19 + 2x = 7

Add '19' to each side of the equation.
-19 + 19 + 2x = 7 + 19

Combine like terms: -19 + 19 = 0
0 + 2x = 7 + 19
2x = 7 + 19

Combine like terms: 7 + 19 = 26
2x = 26

Divide each side by '2'.
x = 13

Simplifying
x = 13

See similar equations:

| 2y-12=-33+3 | | 2x+4=2/3x | | 2x+2=40.3 | | 6+5c=-28 | | ln^2(x)+(5)ln(x)=14 | | 3x^2-90=1362 | | 4.8f+6.4=(-8.48) | | T+106.7=62.3 | | ax-ay=b | | 20-2w=4(15-w) | | 7f+2f=18 | | T+20.4=-15.7 | | -x^2+19x-48=0 | | 0=12x-15 | | v-2v+8=8+2v+v | | -2+5x+7x=-14 | | -x^2+19-48=0 | | -8+88g=56 | | -2=11+3(3(1)-5)-7(1) | | 8=6x+2 | | -6x+13=2f+13 | | 26=14-4x | | 6x+2+x=65 | | 15.75n=378 | | d+2d+3d=12 | | 15w+10=70 | | 70-22=39+x | | 0=12x-5 | | 2x+5*(3x)=510 | | 0.875w=0.50w+0.75w | | 44=9-7x | | 2x+10(2x+20)-10=130 |

Equations solver categories